New Insights into Potential Therapeutic Targets for Neuroendocrine Prostate Cancer: From Bench to Clinic - Maoping Cai; Fengtao Zheng; Yang-Zi Ren; Chuqian Zhen; Dujiang Fu; Xian-Lu Song; Qing Li; Yuanyuan Qu; Zhe-Sheng Chen; Shan-Chao Zhao (Research)
Neuroendocrine prostate cancer (NEPC), an aggressive and highly malignant subtype of castration-resistant prostate cancer (CRPC), arises through drug resistance mechanisms involving genomic alterations, epigenetic remodeling, tumor microenvironment (TME) reprogramming, and lineage plasticity. A hallmark of NEPC is its independence from the androgen receptor (AR) pathway, evidenced by diminished or absent AR expression—a key barrier to effective clinical management. Therefore, a comprehensive understanding of NEPC pathogenesis and progression is essential, as it facilitates the identification of potential therapeutic targets and the development of more effective therapies. In this review, we summarize the typical characteristics of NEPC and describe its clinical diagnosis, relevant imaging modalities, current treatment strategies, and associated therapeutic difficulties. We also highlight the core events driving NEPC formation. Furthermore, we discuss potential therapeutic targets for the disease and review pharmacological agents that have demonstrated efficacy against NEPC, aiming to offer innovative perspectives and potential research directions for future NEPC treatment.